(untitled) (Palíndromo, 2023)
In this article, we will approach performance art, a contemporary artistic genre that invests in crossing the borders between the arts, having the body as a working material. Emerging from the interarts urgency, from the interrelationships between the arts, from the combination and fusion of autonomous art genres, as an indisciplinary gesture, which configures the art of performance. To do so, we will briefly review the concept of performance that imply the broad notions of its studies and practices. In order to provoke a look at performative productions that take place in Brazil, peripheral and marginal, deinstitutionalized and or forgotten/erased in time by canonical narratives, we will compare some exponents of the genre of performance art, according to the history of western and hegemonic art. , some examples of performances, not considered and not legitimized in this context, which can be translated into performance art, from the revised conceptual premises.